Clarifying Water Column Respiration and Sedimentary Oxygen Respiration Under Oxygen Depletion Off the Changjiang Estuary and Adjacent East China Sea - Zhou, Jun; Zhu, Zhuo-Yi; Hu, Huan-Ting; Zhang, Gui-Ling; Wang, Qian-Qian (Frontiers in Marine Science, 2021)
The Changjiang Estuary and its adjacent East China Sea are one of the largest coastal hypoxia sites in the world. The oxygen depletion in the near bottom waters (e.g., a few meters above the seabed) off the Changjiang Estuary is cause by water column respiration (WCR) and sedimentary oxygen respiration (SOR), in which the residual O2 is partially or totally consumed, respectively. Quantification of the WCR and SOR contributions to total apparent oxygen ultilization (AOU) is essential for a better understanding of the occurrence of hypoxia off the Changjiang Estuary. In this work, we conducted a field investigation in July 2018 to collect the water samples for δ18O and O2/Ar ratio analysis. Off the Changjiang Estuary in July 2018, the δ18O of dissolved oxygen in the near bottom waters ranged from 1.039‰ to 8.457‰, generally higher relative to that in the surface waters (–5.366‰ to 2.336‰), indicating fractionation of δ18O during oxygen depletion. Based on an isotope-fractionation based respiration model that quantifies the coupling of δ18O and dissolved oxygen concentration, the WCR% and SOR% in total near bottom AOU is clarified, which indicates that the mean WCR and SOR contributions are 51% and 49%, respectively. In ranges, WCRcontribution to total AOU varied from 23% to 64% and SOR contribution varied from 36% to 77%. The pooled samples that all beneath both the pycnocline and upper mixed layer indicates that WCR contribution (in %) to total AOU increased along with increasing AOU (in μmol/L), whereas reverse situation stands for SOR. Accordingly, we propose that the WCR% and SOR% in total AOU of the near bottom waters is dynamic, not stationary, along with ambient environmental factors changes. SOR is the main factor that determines the background AOU of the near bottom waters off the Changjiang Estuary, but it is instead the WCR that drives the dissolved oxygen level to hypoxic. Sensitivity analysis shows that the proposed dynamic succession between WCR% and SOR% along with AOU is not very sensitive to WCR fractionation factor within a reasonable ɛ range (‒16‰ to ‒25‰).